β-Lactoglobulin–carboxymethylcellulose core–shell microparticles: Construction, characterization and isolation - Carpineti, L. (2014)
The aim of this work was to build, to isolate and to characterize, core–shell microparticles composed of a core of thermally aggregated β-lactoglobulin (β-lg) covered by a shell of carboxymethylcellulose (CMC). The core–shell particles were obtained by mixing (β-lg)n and CMC solutions at pH 7 and finally, decreasing the pH up to 4, promoting the adsorption of CMC on the protein core due their opposite electric charge. The core–shell microparticles were characterized by static laser light scattering (SLS), optical microscopy and atomic force microscopy (AFM). At pH 4, (β-lg)n showed a diameter ∼200 nm, but after adding the polysaccharide had a diameter ∼1 μm. The microscopy corroborated the data obtained by SLS measurements. Core–shell microparticles could be isolated by lyophilization and potentially applied as a fat replacement and/or a delivery systems for encapsulated substances in food formulations.